The role of Arg157Ser in improving the compactness and stability of ARM lipase - Salleh, Abu Bakar; Abd Rahim, Arilla Sri Masayu; Raja Abdul Rahman, Raja Noor Zaliha; Leow, Thean Chor; Basri, Mahiran (Omics Publishing Group, 2012)
Consensus approach is an efficient strategy to identify hot residue important for compactness and stability of protein. Structure of ARM lipase was modeled to explore the possible effect of critical point mutation towards structure and function. The significant difference of amino acid at position 157 between ARM lipase (Arg157) and other thermostable lipases (Ser157) was targeted as a critical residue. Using YASARA software, Arg157 was substituted to Ser and subsequently the energy minimized. Both ARM and R157S lipases were analyzed by MD simulations at different temperatures (50ºC,60ºC, and 70ºC). MD simulation result showed that R157S lipase had lower value of RMSD, RMSF, solvent accessible surface area (SASA) and radius of gyration than native ARM lipase. It indicated that R157S lipase had higher compactness in the structure leading to enhanced stability. To validate the computational data, the substitution of Arg157 to Ser has been conducted using site-directed mutagenesis experimentally. The catalytic efficiency (kcat/KM) of R157S lipase was refold better than ARM lipase of 70°C. Circular dichorism study revealed that R157S lipase had increased thermostability with higher Tm value (71.6°C) than its wildtype (63.9°C) indicating a better compactness as revealed by spectrofluorocence study. Thus the rational design of substituting Arg157 with Ser improved the protein folding of mutant lipase as shown in MD simulations and subsequently increased the catalytic effectiveness and thermodynamic stability.